Advances in dopamine receptor agonists for the treatment of Parkinson's disease. (21st September 2016) - Stocchi, Fabrizio; Torti, Margherita; Fossati, Chiara
ABSTRACT: Introduction: Dopamine agonists (DA) are a class of agents which directly stimulate dopamine receptors mimicking the endogenous neurotransmitter dopamine. At first used as adjunctive therapy in the advanced phases of the disease, over the years a significant role was found for DA monotherapy as a first approach in the initial stage of Parkinson's disease (PD). Several reviews have already reported efficacy and safety of DA in PD and differences between DA and levodopa. Therefore the objective of this review is to gather recent updates in DA therapy. A thorough knowledge of recent literature evidences, would help clinician in the management of treatment with DA. Areas covered: Our review investigates recent updates on DA therapy, the role of these compounds in controlling non-motor symptoms (NMS) as well as new formulations under clinical evaluation and newly emerged post-marketing safety considerations. A literature search has been performed using Medline and reviewing the bibliographies of selected articles. Expert opinion: DA represents a very important option in the treatment of PD, even though there are still some criticisms and unmet needs. A better knowledge of dopamine receptors could lead to identification of new compounds able to better balance clinical efficacy and side effects.